THE CORRELATION BETWEEN STUDENTS GRAMMAR MASTERY AND WRITING ABILITY - Anita Purba; Fitri Indriyani (Program Studi Pendidikan Bahasa Inggris FKIP, 2021)
The Objective of this research was to find out the significant correlation between students’ grammar mastery or language features of recount text and writing recount text ability of the tenth grade of SMK SATRYA BUDI PERDAGANGAN. This research used correlation research design. The population of this research was 88 students and research sample was from X 1 RPL which consisted of 30 students which selected by using cluster sampling technique. Technique of data collection was tests. In analyzing the data, the writer applied Pearson’s Product Moment Correlation Coefficient and Significance of Coefficient Correlation formula. The result of the research showed that tcount is 3,125 and the ttable at significant level 0f 5% (0,05) with 28 degree of freedom (df) was 2,048. It means that tcount is higher than ttable. It can be concluded that alternative hypothesis is accepted and null hypothesis is rejected. It means that there is significant correlation between students’ grammar mastery or language features of recount text and writing recount text ability